Antibiotic Resistance Increases with Local Temperature. (4th October 2017) - MacFadden, Derek; McGough, Sarah; Fisman, David; Santillana, Mauricio; Brownstein, John
Abstract: Background: Antibiotic resistance is considered as one of our greatest emerging public health threats. Current understanding of the factors governing spread of antibiotic-resistant organisms and mechanisms among populations is limited. Methods: We explored the roles of local temperature, population density, and additional factors on the distribution of antibiotic resistance across the United States, using a database of regional antibiotic resistance that incorporates over 1.6 million bacterial pathogens from human clinical isolates over the years 2013–2015. Results: We identified that increasing local temperature as well as population density were associated with increasing antibiotic resistance in common pathogens. An increase in temperature of 10 o C was associated with increases in antibiotic resistance of 4.2%, 2.2%, and 3.6% for the common pathogens Escherichia coli, Klebsiella pneumoniae, and Staphylococcus aureus . The effect of temperature on antibiotic resistance was robust across almost all classes of antibiotics and pathogens and strengthened over time. Conclusion: These findings suggest that current forecasts of the burden of antibiotic resistance could be significant underestimates in the face of a growing population and warming planet. Disclosures: All authors: No reported disclosures.